Project and Analysis of Quasi-Periodic PBG for Microstrip Antenna - Guimarães,Ádller O. (2020)
Abstract In this work the influence of quasi-periodic distributions of air holes with 6, 12 and 6-fold modified symmetries, applied to the substrate of a rectangular microstrip patch antenna are analyzed. To validate the study, parameters such as S11 parameter, bandwidth, total gain, radiation pattern and electric field were investigated through computational simulations. The results obtained for all the PBG structures were compared to each other and to a reference antenna without PBG. In addition, we analyzed the resonating modes of each structure and it was observed improvements in bandwidth and gain for all modified structures when compared with the reference antenna, as well as reduction of the dielectric constant that is also recalculated. Some prototypes were built to compare the computational results to the measured results. It was verified that the measured and simulated results of return loss are in agreement and the antenna with 6-fold modified symmetry presented better performance than the others analyzed PBG structures.